Evaluieren und Prüfen in DaF / DaZ - Ersch, Christina Maria (DaF/DaZ in Forschung und Lehre, 2020)
Consistent evaluation is an important prerequisite for quality assurance and continuous further development in the area of DaF/DaZ. With a focus on virtual learning, this volume deals with the evaluation of the Inverted Classroom Model for the training of teachers of German as a foreign language and specifically with language learning apps. A second focus is on the evaluation of exams and tests. In addition to the medical language examination and the qualification tests of future teachers, the focus here is on examiner qualifications. The critical discussion will present suggestions for solutions as well as new research approaches. This volume does justice to the claim that theory and practice are closely intertwined. Christina Maria Ersch studied German and Scandinavian Studies in Göttingen and German as a foreign language in Mainz, where she is a research assistant. She has been teaching German as a foreign language for several years, is a certified telc examiner and conducts advanced training courses in neurodidactics and action-oriented learning. Her research interests are, among other things, in general didactics with a focus on competence-oriented, digital learning and in intercultural communication.